2015
DOI: 10.1080/0966369x.2014.992117
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: This editorial theorizes the emotional entanglements that constitute spaces of fieldwork. Drawing on Sara Ahmed's notion of sticky and circulating emotions, we develop the concept of emotional entanglements as a way to engage with the methodological implications of the emotional turn in geographic research. Beyond providing empirical evidence for research on emotional geographies, we argue that an attention to emotions in fieldwork has the potential to reinvigorate feminist practices of reflexivity and positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Mc Queeney and Lavelle [7,46] raised similar issues in relation to critical ethnography and our research shows that researchers from across a range of subjects and disciplines involved in broader qualitative methodologies experienced similar tensions. It has been suggested that attending to our emotional reactions can allow us to gain insight into our position as researchers operating within larger power structures [31]. The emotional reactions described here show that the positionality of the researcher within the research power structure was a source of emotional distress in itself.…”
Section: Responsibility For Supporting the Emotional Labourermentioning
confidence: 66%
See 2 more Smart Citations
“…Mc Queeney and Lavelle [7,46] raised similar issues in relation to critical ethnography and our research shows that researchers from across a range of subjects and disciplines involved in broader qualitative methodologies experienced similar tensions. It has been suggested that attending to our emotional reactions can allow us to gain insight into our position as researchers operating within larger power structures [31]. The emotional reactions described here show that the positionality of the researcher within the research power structure was a source of emotional distress in itself.…”
Section: Responsibility For Supporting the Emotional Labourermentioning
confidence: 66%
“…At the time of writing, we note that some moves to respond to this are already evident within the UK, with the establishment of a number of events relevant to emotions in sensitive research. Our study shows that there are many commonalities among researchers working in sensitive topics, therefore we sincerely hope these events become a routine part of the culture of qualitative research and a formal part of relevant national and international conferences, instead of being hidden within informal spaces [31].…”
Section: Responsibility For Supporting the Emotional Labourermentioning
confidence: 71%
See 1 more Smart Citation
“…Conceptually, my approach is inspired by Laliberté and Schurr's (2016) call to (re)-invigorate reflexive practices through a reflexive ethnography of emotions in which the researcher interrogates their own "emotional entanglements" with the 'field.' This enables an enquiry into asymmetrical power relations, questions the ontology of the field and highlights ethical discussions through-out the research process, from ideation and research to writing and dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…To constructively address these issues, I propose to take emotions, specifically fatigue, as the starting point to respond to Laliberté and Schurr's (2016) call for reflexive ethnography to elucidate positionality and power relations and unsettle a tendency for the reproduction of othering categories in migration studies. Fatigue, I suggest, is a constitutive element of the emotional geography in which refugees, humanitarian aid workers, activists and migration researchers move in.…”
Section: Introductionmentioning
confidence: 99%